Bioinspired carbide-derived carbons with hierarchical pore structure for the adsorptive removal of mercury from aqueous solution. Issue 35 (19th April 2017) - Fischer, C.; Oschatz, M.; Nickel, W.; Leistenschneider, D.; Kaskel, S.; Brunner, E.
Abstract : Biosilica of the diatom species Thalassiosira pseudonana is used as hard template for the synthesis of silicon carbide-derived carbons. Abstract : Biosilica of the diatom species Thalassiosira pseudonana is used as hard template for the synthesis of silicon carbide-derived carbons. The typical species-specific macroporous structure is retained during the nanocasting-chlorine treatment process and the resulting materials exhibit very high specific surface areas up to 2300 m 2 g −1 . Bioinspired carbons show very high capacities in mercury adsorption from aqueous solution compared to reference materials.